THE LEGAL POLITICS OF MINING MANAGEMENT IN ACEH AFTER THE ENACTMENT OF LAW NUMBER 3 OF 2020 ON MINERAL AND COAL MINING - Putri Kemalasari; Eza Aulia; M. Nahyan Zulfikar; Ilka Sandela (NEGREI: Academic Journal of Law and Governance, 2025)
Abstract. The enactment of Law Number 3 of 2020 on Mineral and Coal Mining has had an impact on Aceh as a special autonomous region in the management of mining activities. The ratification of this law is considered to be in conflict with Law Number 11 of 2006 on the Governance of Aceh and Government Regulation Number 3 of 2015 concerning National Government Authority in Aceh. Aceh’s special status in the mining sector includes the authority to issue Mining Business Licenses. In response to this issue, the Aceh Government, through letter Number 543/11240, affirmed its stance on maintaining Aceh's special authority in managing mineral and coal mining. Subsequently, the Ministry of Home Affairs issued Letter Number 118/4773/OTDA, reaffirming that the Central Government retains authority to determine Norms, Standards, Procedures, and Criteria (NSPK) related to mining affairs, human resource development supervision, and foreign investment (PMA) matters.This study employs a normative legal research method with a statutory approach. The aim of the study is to examine the legal politics of mining management in Aceh following the enactment of Law Number 3 of 2020, particularly in the context of its special autonomy. The study further seeks to analyze and describe the harmonization of both legal frameworks in determining the special authority of Aceh in mining management. The research findings show that, normatively, the provisions of Law Number 3 of 2020 also apply to the regions of Yogyakarta, DKI Jakarta, Aceh, West Papua, and Papua, insofar as no specific law regulates otherwise for these regions. With the enforcement of this law, Aceh's authority in the mining sector, as previously granted under Law Number 11 of 2006, has been reduced. Based on an Instruction from the Governor of Aceh, mining management in Aceh continues to operate as usual. This is supported by an Instruction from the Ministry of Home Affairs, which confirms that Aceh may disregard provisions of the new law if there are existing regulations specifically governing mineral and coal mining in the region.